The Role of Nutritional and Lifestyle Factors in Musculoskeletal Disorders among Porters - Rivaldy, Wahid; Fitrianingsih, Asti Dewi Rahayu; Kumalasari, Isti; Santanu, Ayu Mutiara (Sarana Ilmu Indonesia (Salnesia), 2025)
Musculoskeletal disorders (MSDs) represent a frequent occupational health issue arising from mechanical stress, particularly repetitive lifting and long periods of standing. These conditions are especially prevalent among workers performing strenuous manual tasks, such as porters. Initial observations at Bandung Railway Station revealed recurring shoulder and calf discomfort reported by porters, suggesting the need to investigate whether nutritional intake, nutritional status, and lifestyle behaviors contribute to these complaints. This research sought to determine the association between nutrient consumption, nutritional status, lifestyle factors, and musculoskeletal disorder (MSDs) symptoms among porters at Bandung Railway Station. The study utilized a quantitative design with a cross-sectional framework. All 67 porters at the station were included through total sampling. Data were gathered through structured interviews using validated tools: the Nordic Body Map to identify MSD symptoms; a 24-hour dietary recall to quantify macro and micronutrient intake; the Pittsburgh Sleep Quality Index (PSQI) to assess sleep patterns; and anthropometric measurements to determine body mass index (BMI). Data analysis showed that sleep quality was the dominant factor (p-value = 0,002), with a 59,6% MSDs prevalence in poor sleepers versus 5% in good sleepers. Carbohydrate intake was also significant (p-value = 0,033), where adequate intake surprisingly recorded higher MSDs (59,3%) than deficient intake (32,5%); thus, MSDs in this study are primarily driven by poor sleep and suboptimal carbohydrate intake.